Brentuximab vedotin in patients with relapsed or refractory Hodgkin lymphoma who are Ineligible for autologous stem cell transplant: A Germany and United Kingdom retrospective study. (16th October 2017) - Bröckelmann, Paul J.; Zagadailov, Erin A.; Corman, Shelby L.; Chirikov, Viktor; Johnson, Courtney; Macahilig, Cynthia; Seal, Brian; Dalal, Mehul R.; Illidge, Tim
Abstract: Objective: Brentuximab vedotin (BV) is an anti‐CD30 antibody‐drug conjugate licensed for the treatment of relapsed/refractory Hodgkin lymphoma (rrHL) following autologous stem cell transplant (ASCT) or at least two prior therapies when ASCT or multiagent chemotherapy is not an option. The objective of this study was to describe real‐world outcomes with BV in patients with rrHL considered ASCT ineligible or who refuse ASCT. Methods: This was a retrospective medical chart review study that enrolled patients ≥18 years old who were initially diagnosed with HL between January 1, 2008 and June 30, 2014, considered ASCT ineligible, and treated in routine care with BV for progressive disease after multidrug chemotherapy regimens. Clinical outcomes included best response to treatment, progression‐free survival (PFS), overall survival (OS), and adverse events. Results: A total of 136 patients were included, with a median age of 70 years at initial HL diagnosis. The most common reasons for ASCT ineligibility were comorbidities (74%) and age (57%). Overall response rate was 74%, and PFS and OS were 15.1 and 17.8 months, respectively. Peripheral neuropathy was observed in 9.6% of patients. Conclusion: The results of this study provide real‐world evidence on the feasibility and effectiveness of BV in elderly or frail ASCT‐ineligible patients with rrHL in a real‐world setting.